HAKIKAT PENDIDIKAN ISLAM TELA’AH MENGENAI MANAJEMEN MUTU PENDIDIKAN ISLAM - Syamsi Syamsi; Syamsuardi Syamsuardi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
The essence of Islamic education is the effort of devout Muslim adults to consciously direct and guide the growth and development of their students' fitrah (basic abilities) through Islamic teachings towards the maximum point of growth and development. Theoretically, education means feeding a person's soul so that they get satisfaction in accordance with Islamic teachings, so it must be a process through institutions and through a curricular system that is guided by Islamic law. Improving the quality of Islamic education is an important first step that must be taken. Quality improvement must be carried out comprehensively by using and empowering all aspects of existing resources. The basic strategy for continuously improving quality is through improving all Garapan objects in the management of Islamic Education, starting from improving educational staff, students, curriculum, learning processes, educational facilities and infrastructure, finances and relations with the community. The process of utilizing human resources and other resources must support the achievement of goals effectively and efficiently based on size, grade, conditions and assessment of the quality of goods or services (products) in accordance with customer satisfaction.